Single equation endogenous binary response models - Andrew Chesher (Centre for Microdata Methods and Practice (cemmap), 2009)
This paper studies single equation models for binary outcomes incorporating instrumental variable restrictions. The models are incomplete in the sense that they place no restriction on the way in which values of endogenous variables are generated. The models are set, not point, identifying. The paper explores the nature of set identification in single equation IV models in which the binary outcome is determined by a threshold crossing condition. There is special attention to models which require the threshold crossing function to be a monotone function of a linear index involving observable endogenous and exogenous explanatory variables. Identified sets can be large unless instrumental variables have substantial predictive power. A generic feature of the identified sets is that they are not connected when instruments are weak. The results suggest that the strong point identifying power of triangular control function models - restricted versions of the IV models considered here - is fragile, the wide expanses of the IV model's identified set awaiting in the event of failure of the triangular model's restrictions.
Keywords: C10; C14; C50; C51; 330; Binary Response; Control functions; Endogeneity; Incomplete models; Index Restrictions; Instrumental variables; Probit Model; Set Identification; Threshold Crossing Models; Triangular Models; Mathematik